Video-assisted thoracic lobectomy for lung cancer in Italy: the 'VATS Group' Project. (December 2016) - Crisci, Roberto; Droghetti, Andrea; Migliore, Marcello; Bertani, Alessandro; Gonfiotti, Alessandro; Solli, Piergiorgio; ,
As part of the third Mediterranean Symposium in Thoracic Surgical Oncology, we introduce the Italian VATS Group (http://vatsgroup.org/sito/index.php ). This national collaborative initiative was established in 2013 and started to recruit patients in January 2014; as of July 2016, 3680 patients have been enrolled in the database. Three different video-assisted thoracic surgery approaches have been predominantly used by Italian thoracic surgery centers, 71% of them preferentially adopting a multi-portal approach, with a 20% recorded morbidity. The majority of the cases were stage I adenocarcinomas of the lung. Conversion to open surgery occurred in 9% of the cases. The study suggests video-assisted thoracic surgery lobectomy as a 'gold standard' for the surgical treatment of early-stage lung cancer in Italy.